Low Concentration H2O2/TiO_N in Office Bleaching: A Randomized Clinical Trial - Bortolatto, J. F. [UNESP]; Pretel, H.; Floros, M. C.; Luizzi, A. C. C. [UNESP]; Dantas, Andréa Abi Rached [UNESP]; Fernandez, E.; Moncada, G.; Oliveira, O. B. de [UNESP] (Sage Publications Inc, 2014)
Objectives: The purpose of this randomized double-blinded clinical trial was to test the efficacy and tooth sensitivity promoted by the use of an in-office 15% H2O2 bleaching agent containing nanoparticles of TiO_N photocatalyzed with LED/laser light (HP15) and a control of 35% H2O2 (HP35). Methods: Forty healthy volunteers, both sexes, aged 18 to 25 yr, were randomly distributed in 2 groups: HP15 (n = 20) was treated in 3 sessions of 48 min each, and HP35 (n = 20) was treated in 3 sessions of 45 min each. The efficacy (E) was evaluated by Delta E values measured via reflectance spectroscopy. The tooth sensitivity (S) was analyzed by visual analog scale (low, average, high, very high). The absolute risk reduction and the number needed to treat index were calculated. The data were analyzed by mixed repeated measures analysis of variance with Bonferroni-correction t test (alpha = 0.05). Results: For the efficacy, significant differences were found for number of bleaching sessions (p = .0001; eta(2)(p) = 0.73 and pi = 1.000) and for the interaction of number of sessions and bleaching protocols (p =.0001; eta(2)(P) = 0.319 and pi = 1.000. The tooth sensitivity level showed significant differences only between the bleaching protocols. Absolute risk reduction calculated was 52% and number needed to treat, 1.92. Conclusions: The bleaching agent with the lower concentration (HP15) promoted lower levels of tooth sensitivity and presented greater efficacy compared to the control (HP35) in patients between 18 and 25 yr old. The limitation of short-term evaluation did not provide information about the longevity of the tooth bleaching
Keywords: tooth bleaching; hydrogen peroxide; nanotechnology; titanium dioxide; dentin sensitivity; clinical protocols